2011
DOI: 10.1002/jor.21347
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between adolescent idiopathic scoliosis and previously reported single nucleotide polymorphisms in MATN1, MTNR1B, TPH1, and IGF1 in a Japanese population

Abstract: Adolescent idiopathic scoliosis (AIS) is a spinal deformity most commonly arising in apparently healthy girls around puberty. AIS has a strong genetic predisposition. Several genetic associations between AIS and single nucleotide polymorphisms (SNPs) have been reported; common SNPs in the genes for matrilin 1 (MATN1), melatonin receptor 1B (MTNR1B), tryptophan hydroxylase 1 (TPH1), and insulin-like growth factor 1 (IGF1) are reported to be associated with AIS in Chinese. However, these associations have not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
40
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 32 publications
1
40
0
5
Order By: Relevance
“…21 The associations of these two genes with scoliosis have not been replicated in the Japanese population. 30 In our study, we successfully replicated the previous GWAS finding that rs11190870 was highly significantly associated with AIS, which suggests that this SNP or the variants in linkage disequilibrium with this SNP may have an important role in the etiology of AIS. This is the first SNP associated with AIS that has been definitively replicated in another population.…”
Section: Discussionsupporting
confidence: 84%
“…21 The associations of these two genes with scoliosis have not been replicated in the Japanese population. 30 In our study, we successfully replicated the previous GWAS finding that rs11190870 was highly significantly associated with AIS, which suggests that this SNP or the variants in linkage disequilibrium with this SNP may have an important role in the etiology of AIS. This is the first SNP associated with AIS that has been definitively replicated in another population.…”
Section: Discussionsupporting
confidence: 84%
“…A total of 2,142 AIS-affected subjects were recruited for the GWAS from ten collaborating hospitals (Japanese Scoliosis Clinical Research Group), according to the criteria previously described. 7,8,12 All underwent clinical and radiologic examinations by expert scoliosis surgeons. 11,144 control subjects for the GWAS were drawn from the BioBank Japan Project (see Web Resources) and its related projects, as previously described.…”
mentioning
confidence: 99%
“…It is likely that this polymorphism could affect the gene expression of MT2, thus accounting for the lower mRNA expression level of MT2 found in AIS patients in the current study. The results of Qiu’s study could not be reproduced by a few related studies [5356], which might partly be explained by the different ethnic populations [5456] recruited for the studies. It is recognized that the ratio of combinations of the SNP of interest is different among different ethnic groups (Hapmap).…”
Section: Resultsmentioning
confidence: 75%
“…However, not all the AIS patients in this study showed a low expression of MT2, implying the heterogeneity of the disease and the presence of etiologies other than melatonin signaling dysfunction. The heterogeneous nature of AIS may also explain why associated common variants near melatonin receptor genes have not yet been identified in association studies [56]. …”
Section: Resultsmentioning
confidence: 99%